(untitled) (ItalianoLinguadue, 2009)
Il contributo, incentrato sul tema dell’italianismo francese in prospettiva lessicografica tra storia, etimologia e cultura, tocca problemi generali del prestito (origini, adattamento formale e semantico, percorsi linguistici, fonti) e particolari ( come quello del passaggio dal nome proprio al nome comune). The article deals with Italianisms in French from a lexicographical perspective embracing history, etymology and culture and involving general issues of borrowing (origins, formal and semantic adaptations, linguistic paths, sources) as well as more specific ones (such as the shift from proper names to common nouns).